Penerapan Metode Sorogan dalam Meningkatkan Kemampuan Membaca Kitab Kuning Santri Mahasiswa - Muhammad Yusuf Maulana Reksa; Huriah Rachmah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. X Islamic Boarding School is an Islamic boarding school that prioritizes yellow learning, using the bandongan method, besides that X Islamic Boarding School uses the sorogan method to improve the ability of students to read the yellow book. Therefore, the authors are interested in conducting research on